Geochemistry of Paleozoic Dadas Shales from the Foreland of Southeastern Turkey, Bismil, Diyarbakir - Akkoca, Dicle Bal; Isik, Umit (Edizioni Nuova Cultura, 2018)
The Early Silurian-Early Devonian Dadas Shales are composed of sandstone-banded, carbonate-interbedded shales and organic material-rich shales. The sediment geochemistry, along with mineralogical investigations of two core samples from Dadas Shales have been carried out in order to understand their provenance, paleoweathering, paleoredox, paleoclimate and tectonic conditions. Samples are mainly composed of feldspars, quartz, clay minerals, calcite and dolomite. Chemical index of alteration (CIA) indices reflects medium weathering. Th/Sc and low Zr/Sc ratios suggest no (or at least minor) sediment recycling and sorting. The C-values of Dadas Shales show mainly moist climatic conditions prevailed during Early Silurian-Early Devonian. Ni/Co vs V/Cr, U/Th, Cu/Zn, Ce/Ce anomaly yielded oxic depositional conditions. The provenance discrimination diagram show magmatic and partly sedimentary provenance for Dadas Shale. Th/U, Rb/Sr, La/Ni, Cr/Th, La/Yb, Eu/Eu*, (La/Yb)(N), (Gd/Yb)(N) ratios and the chondrite-normalized REE patterns of the Dadas Shales are similar to that of Post Archaean Australian Shale (PAAS), and those of Upper Continental Crust (UCC). Source rock composition vary from felsic to neutral and higher values of Sc/Th, Cr/Th, Co/Th in Dadas Shales with respect to sands from silicic rocks may show the presence of relatively higher proportion of basic material in their source. The provenance discrimination diagram, La/Th versus Hf diagram also show mixed felsic/basic source fields. According to new discriminant-function multi-dimensional diagram for low-silica elastic sediments, Dadas Shales are plotted within the continental rift field.
Keywords: Paleozoic; Dadas Shales; provenance; climatic conditions; southeastern Turkey